ANALISIS RASIO KEUANGAN DALAM MEMPREDIKSI PERUBAHAN LABA PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI - Novasari, Multia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the influence of current ratio, quick ratio, debt to total assets ratio, total assets turn over, net profit margin and return on equity to the profit changes on automotive companies which are listed in Indonesia Stock Exchange. Multiple linear regression analysis is used in this research as analysis technique. The samples are 9 companies with criteria the automotive companies which continuously issue their financial statement from 2008 to 2012 and publish their financial statement in the form of Rupiah currency.The examination result of R Square (R2) is 0.383 or 38.30% which means that the contribution of independent variables which consist of current ratio, quick ratio, debt to total assets ratio, total assets turn over, net profit margin and return on equity have an influence to the profit changes is 38.30% while the remaining is 61.70% which is influenced by other variable.The examination result of regression coefficient significance Î±, only net profit margin variable has significant influence to the profit changes while current ratio, quick ratio, debt to total assets ratio, total assets turn over and return on equity have no significant influence to the profit changes.Keywords: Financial Ratio, Profit Changes, Financial Report.